2022
DOI: 10.1183/13993003.00910-2022
|View full text |Cite
|
Sign up to set email alerts
|

In critically ill patients, anti-anaerobic antibiotics increase risk of adverse clinical outcomes

Abstract: BackgroundCritically ill patients routinely receive antibiotics with activity against anaerobic gut bacteria. Yet in other disease states and animal models, gut anaerobes are protective against pneumonia, organ failure, and mortality. We therefore designed a translational series of analyses and experiments to determine the effects of anti-anaerobic antibiotics on the risk of adverse clinical outcomes among critically ill patients.MethodsWe conducted a retrospective single-center cohort study of 3032 critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 81 publications
8
32
0
1
Order By: Relevance
“…Although rectal swabs were collected within 48 h after hospital admission, different treatment modalities could have contributed to gut microbiota differences between ICU and ward patients. Even short courses of antibiotics may alter the gut microbiota composition, and in particular, anti-anaerobic antibiotics have been shown to increase mortality in ICU patients, possibly due to effect on gut and airway microbiota [ 32 ]. Also dexamethasone could impact the gut microbiota composition and has been reported to interfere with gut permeability [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although rectal swabs were collected within 48 h after hospital admission, different treatment modalities could have contributed to gut microbiota differences between ICU and ward patients. Even short courses of antibiotics may alter the gut microbiota composition, and in particular, anti-anaerobic antibiotics have been shown to increase mortality in ICU patients, possibly due to effect on gut and airway microbiota [ 32 ]. Also dexamethasone could impact the gut microbiota composition and has been reported to interfere with gut permeability [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Head-to-head comparison has shown SDD to be superior to SOD in reducing VAP incidence and improving clinical outcomes including mortality. Empiric administration of antianaerobic antibiotics in critically ill patients was recently shown to be associated with decreased overall survival, increased risk of VAP, and enrichment by pathogenic Enterobacteriaceae in gut microbial communities and respiratory cultures diagnostic of VAP [23 ▪▪ ]. This randomized and observational evidence defies conventional thinking that VAP mostly develops due to contiguous spread of upper respiratory tract pathogens into the lower respiratory tract and highlights the gut as a probable pool of pathogens for secondary infections in the ICU [21 ▪▪ ].…”
Section: Empirical Evidence Indicative Of Gut–lung Axis In Critical I...mentioning
confidence: 98%
“…A common issue in critical care practice is the extensive use of often empiric, broad-spectrum antibiotics. Recent retrospective research in critically ill patients has shown that use of antianaerobic antibiotics is associated with decreased overall survival and increased risk of VAP, with detectable impact on gut microbial communities and lower respiratory tract microbiology [23 ▪▪ ]. Such research shows that even when governed by principles of targeting and stewardship, clinical choices on antibiotics from different classes are undertaken with limited appreciation of their off-target effects on the gut microbiome.…”
Section: Conclusion – the Road Towards Therapeutic Manipulation Of Th...mentioning
confidence: 99%
“…When administered empirically in clinical practice, both antibiotics are commonly considered to have comparable activity against gram-negative organisms, including Pseudomonas, although cefepime does not cover anaerobic organisms and piperacillin–tazobactam does. Whether coverage of anaerobic organisms in acutely ill patients is associated with higher3 mortality, lower4–7 mortality or no difference in mortality is uncertain.…”
Section: Introductionmentioning
confidence: 99%